PEMBANGUNAN KUALITAS MANUSIA MELALUI SEKTOR PENDIDIKAN MENYONGSONG PELUANG BONUS DEMOGRAFI DI KOTA PONTINAK - B21109028, HERLINDA (Jurnal Pembangunan dan Pemerataan, 2016)
Human resource development as a development tool should work well as improving the quality of education using school participation, rate so that the window of opportunity that is not free it is utilized and does not cause problems for the resilience of nations in the future, the goverment should prepare carefully from now on in order to achieve demographic bonus. The methodology used is secondary data published by the central statistical agency and national education departments of the city Pontianak, then the data is analyzed. The results showed that the increase in aspects of the school that a student teacher ratio, school roads, facilities and inftastructure can still be quite good. These results became important for the goverment to make decion that both the development of physical and non-physical, it gives positive impact on development in the edeucationn sector. Keyword: Human Resources, Enrollment Rates, Demographic Bonus